Pengembangan Bahan Ajar Berbasis Proyek Di SMA Negeri 2 Lintongnihuta pada materi Asam dan Basa - Jamalum Purba; Novelyani Siregar (Universitas Negeri Medan, 2020)
This study aims to determine the feasibility of project-based chemical teaching materials and increase student learning outcomes on acid-base material using project-based teaching materials and adobe flash multimedia at SMA Negeri 2 Lintongnihuta. This type of research is research and development. This study uses a one-group pretest-posttest design. Data were processed descriptively, obtained the average value of the validation of the modules developed, namely the content eligibility of 3.62; presentation 3.67; language 3.72; and graphic 3.72; with an average of 3.68. Data collection techniques for student learning outcomes by providing pretest and post-test. For the pretest data the experimental class was 48.11 and the repetition class was 46.47, while the post-test data were the experimental class 84.11 and the repetition class 81.32. The mean percentage of improvement in student learning outcomes in the experimental class was 68% and the repetition class was 65%. Hypothesis testing with the right-side t test at the level of α = 0.05 obtained> (7.99> 1.697 (experimental) and 6.65> 1.697 (repetition)) which means that the chemical module integrated project-based learning with adobe flash multimedia developed it is good and in accordance with BSNP criteria standards and is suitable for use.